Phytoplankton pigment and phytoplankton group chlorophyll-a concentrations during POLARSTERN cruise PS131 from North Sea to East Greenland Sea in 29. June to 3. August 2022 from HPLC analysis of water - Astrid Bracher; Hongyan Xi; Christian Hohe (PANGAEA, 2025)
Phytoplankton pigments were determined in the water surface (from 0 to 11 m depth) of a transect from the North Sea to East Greenland Sea and back during RV Polarstern expedition PS131 from 29 Jun to 3 Aug 2022. Water samples were collected from CTD Niskin bottles at five to six different depths from the upper 100 m at CTD stations and from underway sampling. Between 0.4 to 3.5 L of each seawater sample was filtered through Whatman GF/F filters. The sample filters were then shock-frozen in liquid N2 and kept at -80 °C until analysis. High Pressure Liquid Chromatography (HPLC) was performed to quantify various phytoplankton pigments (see Table 1 in Taylor et al. 2011) following the method of Barlow et al. (1997) that was adjusted to our temperature-controlled instruments as detailed in Alvarez et al. (2022). Data were used to analyse the Fram Strait phytoplankton community composition dynamics in Bracher et al. (submitted to DSR-II).